Fihrist-i nuskhahā-yi khaṭṭi-yi Kitābkhāna-yi ʿumūmi-yi Jamʿiyyat-i nashr-i farhang-i Rasht - Rūshan, Muḥammad (Miras Maktoob, ISBN: 9789004365452., 2019)
The library of the "Society for the Advancement of Culture of Gilan" in Rasht was one of the first public libraries in Iran. A private initiative, it took the society seven years from its foundation until the completion of its library in 1934. Besides contributions and gifts, the library now also receives financial support from the municipality of Rasht. The library has a manuscript department which at the time of publication of the present catalogue contained 594 items, 77 of which are collective volumes. In view of the fact that this library has no budget to speak of, it is surprising what interesting items it contains, probably all acquired through local donations. Thus one finds volume two of the Qajar translation of A. Grisolle, Traité élémentaire et pratique de pathologie interne (Paris, 1844, many reprints) (no. 45), and also a collective volume of 22 philosophical texts by Aristotle, Farabi, Avicenna, Tusi, and others (no. 416)